2023
DOI: 10.3390/rs15092383
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Urbanization on Regional Rainfall-Runoff Processes: Case Study in Jinan City, China

Abstract: Rapid urbanization has altered the regional hydrological processes, posing a great challenge to the sustainable development of cities. The TVGM-USWM model, a new urban hydrological model considering the nonlinear rainfall-runoff relationship and the flow routing in an urban drainage system, was developed in this study. We employed this model in the Huangtaiqiao drainage basin of Jinan City, China, and examined the impact of land cover changes due to urbanization on rainfall-runoff processes. Two urbanization s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Based on the hourly rainfall data retrieved from the National Basic Weather Station Beijing Nanjiao Observatory (54,511) from 2010 to 2019 and considering the classification guideline of recognizing the next rain event if no rainfall has occurred for more than 10 h [55], a total of 631 rainfall events were obtained, and the average number of rainfall events per year in Beijing was chosen as 63.1. Unlike many studies that use the return periods as the grading methods [56,57], this study uses 24-h rainfall for the division. According to the meteorological department's standard classification, rainfall between 0.1 mm to 9.9 mm in 24 h is considered light rain, between 10.0 mm to 24.9 mm is moderate rain, between 25.0 mm to 49.9 mm is heavy rain, and greater than 49.9 mm is a rainstorm.…”
Section: Overview Of the Study Areamentioning
confidence: 99%
“…Based on the hourly rainfall data retrieved from the National Basic Weather Station Beijing Nanjiao Observatory (54,511) from 2010 to 2019 and considering the classification guideline of recognizing the next rain event if no rainfall has occurred for more than 10 h [55], a total of 631 rainfall events were obtained, and the average number of rainfall events per year in Beijing was chosen as 63.1. Unlike many studies that use the return periods as the grading methods [56,57], this study uses 24-h rainfall for the division. According to the meteorological department's standard classification, rainfall between 0.1 mm to 9.9 mm in 24 h is considered light rain, between 10.0 mm to 24.9 mm is moderate rain, between 25.0 mm to 49.9 mm is heavy rain, and greater than 49.9 mm is a rainstorm.…”
Section: Overview Of the Study Areamentioning
confidence: 99%
“…The risk reduction and sustainable management of natural resources necessitate periodic assessment to avoid adverse natural and anthropogenic effects [10][11][12]. Water resource management and flood hazard assessments are becoming increasingly critical in arid and semi-arid areas because of climate change and urbanization accompanied by land cover/land use changes [9,[13][14][15][16][17]. Effective water management and disaster mitigation measures are greatly hindered by weather variability, particularly severe events, including extreme rainfall, storm events, and long-ongoing droughts [14,18].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid growth of urbanization has increased the basin's impervious area, reducing rainfall infiltration and increasing the flood risk [3,4]. Zhao et al [5] found that urbanization would cause an increase in flood peak and flood volume, which has a significant amplification effect on designed flood. As urbanization levels rise, there is a more significant increase in the trend of flood peak and flood volume, which can result in a greater expansion of the flood risk areas [6].…”
Section: Introductionmentioning
confidence: 99%